Mpox Virus: A holistic review of molecular pathogenesis, diagnostic advancements, and global response strategies (Acta Scientiarum. Biological Sciences, 2026)
Mpox or Mpox virus (MPXV) has re-emerged as a global health concern, underscoring the importance of understanding its biology, improving diagnostic capacity, and developing effective therapeutic and preventive strategies. This review synthesizes current knowledge of MPXV pathogenesis, highlighting how the virus manipulates host immune responses and adapts through genetic variability. We discuss the spectrum of diagnostic tools, ranging from polymerase chain reaction (PCR) as the gold standard to rapid antigen-based assays and emerging biosensor platforms that enable sensitive and point-of-care detection. Advances in vaccine development and therapeutic repurposing are examined, alongside the challenges of equitable global access. Particular emphasis is placed on the integration of biosensing technologies with genomic surveillance to enhance outbreak preparedness. By bridging insights from virology, diagnostics, and public health, this review provides a comprehensive framework for strengthening global responses to MPXV and guiding future research toward pandemic readiness.